GTN-P: 41 years of Mean Annual Ground Temperature (MAGT) across latitudinal and elevational gradients in the Northern Hemisphere, v1.0 - Mareike Wieczorek; GTN-P; Antoni G Lewkowicz; Alexander L Kholodov; Vladimir E Romanovsky; Dmitry Nicolsky; Dmitry A Streletskiy; Julia Boike; Birgit Heim; Annett Bartsch; Boris K Biskaborn; Hanne Hvidtfeldt Christiansen; et al. (PANGAEA, 2025)
The Global Terrestrial Network for Permafrost (GTN-P) established by the International Permafrost Association (IPA) and WMO under the GCOS and GTOS networks is the primary international global program for monitoring the permafrost Essential Climate Variables (ECVs). Permafrost temperature (Ground Temperature, GT) is formulated as one important ECV by WMO and GCOS. The presented data collection consists of 41 years (1980 - 2021) of annual time series of Mean Annual Ground Temperature (MAGT) from 311 stations and in various depths from 0 to 20 m covering the Northern Hemisphere. It is built from various sources, namely GTN-P GT, exported from the GTN-P database (http://gtnpdatabase.org/boreholes) with last access May 2024, GTN-P MAGT close to the Zero Annual Amplitude ZAA (GTN-P (2018, 2021)), Boike et al (2019, 2020) and data from A. Lewkowicz (University of Ottawa, CA) and A. Kholodov (University of Fairbanks, AK). While field work, station installation and data read-out and the processing to specific temporal averages is being conducted by GTN-P members, the presented data collection of MAGT time series were created from the wide range of the available specific temporal measurement frequencies and calculated averages and measurement depths. The data consists of standardised MAGT per Depth (GTD) from 1980 to 2021, with depths at 0, 0.1, 0.2, 0.25, 0.4, 0.5, 0.6, 0.75, 0.8, 1.0, 1.2, 1.5, 1.6, 2.0, 2.4, 2.5, 3.0, 3.2, 4.0, 5.0, 10.0, 15.0 and 20.0 m. Yearly means were not calculated if >20 % of yearly values are not available or if more than one complete month is missing. An exception was made for data at the depth of Zero Annual Amplitude (ZAA) that represents a valid annual value as there is zero seasonal variation in GT at this depth. The data provided here has been assembled from the original data sources and optimized by the validation team in the ESA Permafrost_cci project for the validation of the Permafrost_cci GTD time series maps.